Abnormal Glucose Metabolism in Male Mice Offspring Conceived by in vitro Fertilization and Frozen-Thawed Embryo Transfer - Qin, Ningxin; Zhou, Zhiyang; Zhao, Wenlong; Zou, Kexin; Shi, Weihui; Yu, Chuanjin; Liu, Xia; Dong, Zehan; Mao, Yiting; Liu, Xinmei; Sheng, Jianzhong; Ding, Guolian; et al. (Frontiers in Cell and Developmental Biology, 2021)
Frozen and thawed embryo transfer (FET) is currently widely applied in routine assisted reproductive technology (ART) procedure. It is of great necessity to assess the safety of FET and investigate the long-term effect including glucose metabolism on FET-conceived offspring. The mouse model is a highly efficient method to figure out the relationship between the process of FET and offspring health. In this study, we obtained mouse offspring of natural conception (NC), in vitro fertilization (IVF), and FET. Glucose and insulin tolerance test (GTT/ITT) were performed on both chow fed or high fat diet (HFD) fed offspring to examine the glucose metabolism status. We detected hepatic PI3K/AKT pathway by western blotting and transcriptome status by RNA-sequencing. Impaired glucose tolerance (IGT) and decreased insulin tolerance were occurred in FET conceived male offspring. After challenged with the HFD-fed, male offspring in FET group performed earlier and severer IGT than IVF group. Furthermore, higher HOMA-IR index and higher serum insulin level post glucose injected in FET-chow group suggested the insulin resistance status. The PI3K/AKT signaling pathway, the major pathway of insulin in the liver, were also disrupted in FET group. Transcriptomics of the liver reveals significantly downregulated in glucose metabolic process and insulin resistance in the FET-chow group. In our study, FET-conceived male mouse offspring presented glucose metabolism dysfunction mainly manifesting insulin resistance. The hepatic insulin signaling pathway were in concordance with reduced glycogen synthesis, increased glycolysis and enhanced gluconeogenesis status in FET-conceived male offspring.